Labour out of Control: The Political Economy of Capitalist and Ethical Organizations. Issue 12 (December 2015) - O'Neil, Mathieu
Digitally networked voluntary associations such as free software projects and Wikipedia can be distinguished from capitalist firms in two respects. First, their predominant logic is 'ethical'. Participation is primarily motivated by self-fulfilment and validated by a community of peers, rather than by earning wages. Second, their governance is 'modular', understood in a design sense (decomposable blocks sharing a common interface), but also in political economy terms: participants oppose restricted ownership and control by individually socializing their works into commons. In recent years capitalist-centralized firms have increasingly engaged with ethical-modular organizations, in some cases paying wages to participants (such labour is thus both 'alienated' or sold, and 'communal', as workers freely cooperate to produce commons). This article reviews the literature dealing with the relationship of these two organizational types. It argues that the manner in which scholars approach a central characteristic of ethical-modular organizations – participants relinquish exclusive property rights over the resource they have created – leads to highly diverse interpretations. Four hypotheses are presented. A 'panoptic' view overlooks the abjuration of exclusive property rights, so that ethical-modular organizations can be defined as a variant of the evolution of capitalist firms into post-bureaucratic networks. 'Skeptics' view this abjuration as irrelevant, and ethical-modular organizations as increasing worker exploitation. In contrast, 'activists' celebrate the abjuration of exclusive property rights, and present ethical-modular organizations as key actors in a historical process leading to the disappearance of capitalism and hierarchy. Finally 'reformists' suggest that the co-optation of communal labour by firms will benefit business practices and society. The article examines the analytical focus of each hypothesis in terms of labour, loss of control by firms over workers, and societal impact. Where appropriate, it raises questions and objections. The conclusion addresses communal labour's effective dependence on capitalist-centralized firms and suggests factors which may contribute to its emancipation.